Involvement of Transforming Growth Factor-β-Associated Kinase 1 in Fixed Airway Obstruction in Asthmatic Patients with Longer Disease Duration Independent on Airway Eosinophilia - Maneechotesuwan K. (2023)
Objective: Transforming growth factor-β-associated kinase 1 (TAK1) mediates non-canonical TGF-β signalling by promoting adhesive, migratory, proliferative and contractile responses of fibroblasts to TGF-β1. However, TAK1 expression status in asthmatic patients with or without fixed airway obstruction (FAO) is unknown. Patients and Methods: A total of 60 adult asthmatics with FAO were recruited and compared to 43 those without FAO (nFAO). TGF-β1 concentrations, and total TAK1 and phosphorylated TAK1 (p-TAK1) levels were determined in sputum supernatants, cytospin, and whole cell lysate by ELISA, immunocytochemistry, and Western blot analysis, respectively, in asthmatics with and without FAO. Results: Asthmatic patients with FAO had much greater sputum TGF-β1 concentrations than those without FAO. This was independent of airway eosinophilia as there was no significant difference in TGF-β1 levels between high and low eosinophil counts within FAO and nFAO groups. In contrast, patients with FAO in the presence of sputum eosinophilia had greater expression of TAK1 and p-TAK1 than those without sputum eosinophilia (P=0.0032 and P=0.0061, respectively). The Western Blot data of total TAK1 and p-TAK1 were consistent with the immunocytochemistry, showing upregulation in all sputum cell types (neutrophils, eosinophils, macrophages, lymphocytes and airway epithelial cells). In addition, total TAK1 expression negatively correlated with pre- and post- bronchodilator FEV1/FVC ratio. Conclusion: TAK1 may play a key role in asthmatic patients with fixed airway obstruction, which was independent of eosinophilic airway inflammation. The interruption of TAK1 might have favourable clinical impact.